Signs of Everyday Life in Linguocultural Studies - G. V. Tokarev (Научный диалог)
The article is dedicated to the linguocultural analysis of the phenomenon of everyday life, which refers to the segment of ordinary culture that encompasses the present time. The sources of the study were V. V. Veresaev’s “Memories”, G. I. Uspensky’s essays “Customs of Rasteryaev Street”, S. A. Tolstoy’s diaries, Tula newspapers, and toponyms. The study was conducted using discourse, conceptual analysis, and linguocultural interpretation methods. Culturally marked signs of everyday life were identified, including determination by the present, orientation towards the usual and standard, and precedent character. It was found that everyday life is segmented depending on the interpreter’s qualities and properties. It reflects norms and prohibitions. It is shown that everyday life is ordinary, stable, and at the same time transient, reflects naive consciousness, and is filled with a large array of cultural attitudes, stereotypes, and scenarios. Everyday life forms the basis for evaluating which people follow based on the principles of “this is how it is done” and “this is how it should be”. The semiotic aspect is considered, represented by various human practices and sign sets that are familiar to them. Typical verbal texts expressing everyday life were identified, including memoirs, diaries, travel notes, and newspapers. It is concluded that everyday life is related to identity since it is perceived by the cultural subject as their own, understandable space.